Dexmedetomidine Use in Critically Ill Children With Acute Respiratory Failure*. Issue 12 (December 2016) - Grant, Mary Jo C.; Schneider, James B.; Asaro, Lisa A.; Dodson, Brenda L.; Hall, Brent A.; Simone, Shari L.; Cowl, Allison S.; Munkwitz, Michele M.; Wypij, David; Curley, Martha A. Q.
Abstract : Objective: Care of critically ill children includes sedation but current therapies are suboptimal. To describe dexmedetomidine use in children supported on mechanical ventilation for acute respiratory failure. Design: Secondary analysis of data from the Randomized Evaluation of Sedation Titration for Respiratory Failure clinical trial. Setting: Thirty-one PICUs. Patients: Data from 2, 449 children; 2 weeks to 17 years old. Interventions: Sedation practices were unrestrained in the usual care arm. Patients were categorized as receiving dexmedetomidine as a primary sedative, secondary sedative, periextubation agent, or never prescribed. Dexmedetomidine exposure and sedation and clinical profiles are described. Measurements and Main Results: Of 1, 224 usual care patients, 596 (49%) received dexmedetomidine. Dexmedetomidine as a primary sedative patients ( n = 138; 11%) were less critically ill (Pediatric Risk of Mortality III-12 score median, 6 [interquartile range, 3–11]) and when compared with all other cohorts, experienced more episodic agitation. In the intervention group, time in sedation target improved from 28% to 50% within 1 day of initiating dexmedetomidine as a primary sedative. Dexmedetomidine as a secondary sedative usual care patients ( n = 280; 23%) included more children with severe pediatric acute respiratory distress syndrome or organ failure. Dexmedetomidine as a secondary sedative patients experienced more inadequate pain (22% vs 11%) and sedation (31% vs 16%) events. Dexmedetomidine as a periextubation agent patients ( n = 178; 15%) were those known to not tolerate an awake, intubated state and experienced a shorter ventilator weaning process (2.1 vs 2.3 d). Conclusions: Our data support the use of dexmedetomidine as a primary agent in low criticality patients offering the benefit of rapid achievement of targeted sedation levels. Dexmedetomidine as a secondary agent does not appear to add benefit. The use of dexmedetomidine to facilitate extubation in children intolerant of an awake, intubated state may abbreviate ventilator weaning. These data support a broader armamentarium of pediatric critical care sedation.